2021
DOI: 10.1007/s13258-021-01151-7
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy induced by H. pylori VacA regulated the survival mechanism of the SGC7901 human gastric cancer cell line

Abstract: Background Vacuolating cytotoxin (VacA) is an important virulence factor of Helicobacter pylori (H. pylori). It was previously believed that VacA can trigger the cascade of apoptosis on mitochondria to lead to cell apoptosis. Recently, it was found that VacA can induce autophagy. However, the molecular mechanism by which VacA induces autophagy is largely unknown. Objective We aimed to explore the molecular mechanism of autophagy induced by H. pylori in gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The mechanisms underlying autophagy induction by H. pylori or HPCF are complex ( 21 ). Two virulence factors, vacuolating cytotoxin (VacA) and cytotoxin-associated gene A (CagA), play very important roles in autophagy ( 21 23 , 34 , 41 , 42 ). Considering plenty of studies have shown that VacA can damage mitochondria and destroy the mitochondrial membrane potential (MMP), the first event we wanted to know was whether mitophagy is involved ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying autophagy induction by H. pylori or HPCF are complex ( 21 ). Two virulence factors, vacuolating cytotoxin (VacA) and cytotoxin-associated gene A (CagA), play very important roles in autophagy ( 21 23 , 34 , 41 , 42 ). Considering plenty of studies have shown that VacA can damage mitochondria and destroy the mitochondrial membrane potential (MMP), the first event we wanted to know was whether mitophagy is involved ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pan Zhu et al reported that VacA could induce autophagy and increase cell death via numerous dilated numerous endoplasmic reticula (ER), increase the eukaryotic translation initiation factor 2 subunit 1 phosphorylation, and also increase expression of tribbles pseudokinase homolog 3 (TRIB3) upon ER stress in AGS cells [ 133 ]. Similarly, increased ROS levels and BECN1, ATG7, and PIK3C3 mRNA expressions were observed following VacA protein treatment in SGC7901 cells, which facilitated a significant decrease in proliferation and an increase in autophagy [ 134 ]. Studies have also shown that CagA and VacA can inhibit autophagy signaling upstream along with autophagy-lysosome maturation, inhibiting gastric autophagy in precancerous lesions of GC.…”
Section: The Relationship Between H Pylori Virulen...mentioning
confidence: 99%
“…In addition, it affects the cell migration and differentiation of the GHCs ( Bussière et al, 2005 ). Recent studies have indicated that VacA, a key toxin of inducing autophagy and apoptosis, can be considered as a marker to predict the risk of gastric carcinogenesis in animal models ( Carlosama-Rosero et al, 2021 ; Luo et al, 2021 ).…”
Section: Helicobacter Pylori Virulence Factorsmentioning
confidence: 99%